ANALYSIS OF THE DEVELOPMENT PROCESS OF THE TERRITORIAL PRODUCTIVE AND TECHNOLOGICAL POTENTIAL OF THE REGION’S CONSTRUCTION ORGANIZATIONS - Bredikhin, Vladimir Viktorovich (Journal of Applied Engineering Science, 2019)
One of the most important economic tasks of construction activities actors is the correct estimation of their initial state in terms of the possibilities for further development. The solution of these complex problems under the conditions of limited resources puts forward the problem of quantitative and qualitative measurement of available resources and productive and technological potential of organizations. The paper discusses a system analysis of the construction organization and the components of the productive and technological potential as subsystems that have a qualitative and quantitative measurement of the maximum possible efficiency of resources usage by a construction organization under conditions of the rational construction management and the interaction of business entities in the investment sector.